Melioidosis: misdiagnosed in Nepal - Shrestha, N; Adhikari, M; Pant, V; Baral, S; Shrestha, A; Basnyat, B; Sharma, S; Sherchand, J (BioMed Central, 2019)
BACKGROUND: Melioidosis is a life-threatening infectious disease that is caused by gram negative bacteria Burkholderia pseudomallei. This bacteria occurs as an environmental saprophyte typically in endemic regions of south-east Asia and northern Australia. Therefore, patients with melioidosis are at high risk of being misdiagnosed and/or under-diagnosed in South Asia. CASE PRESENTATION: Here, we report two cases of melioidosis from Nepal. Both of them were diabetic male who presented themselves with fever, multiple abscesses and developed sepsis. They were treated with multiple antimicrobial agents including antitubercular drugs before being correctly diagnosed as melioidosis. Consistent with this, both patients were farmer by occupation and also reported travelling to Malaysia in the past. The diagnosis was made consequent to the isolation of B. pseudomallei from pus samples. Accordingly, they were managed with intravenous meropenem followed by oral doxycycline and cotrimoxazole. CONCLUSION: The case reports raise serious concern over the existing unawareness of melioidosis in Nepal. Both of the cases were left undiagnosed for a long time. Therefore, clinicians need to keep a high index of suspicion while encountering similar cases. Especially diabetic-farmers who present with fever and sepsis and do not respond to antibiotics easily may turn out to be yet another case of melioidosis. Ascertaining the travel history and occupational history is of utmost significance. In addition, the microbiologist should be trained to correctly identify B. pseudomallei as it is often confused for other Burkholderia species. The organism responds only to specific antibiotics; therefore, correct and timely diagnosis becomes crucial for better outcomes.